ISLAMIC CHARACTER VALUES IN ECOLOGICAL EDUCATION PRACTICES AT SANGGAR ANAK ALAM (SALAM) NITIPTAYAN BANTUL - Rifatul Anwiyah; Azam Syukur Rahmatullah; Aris Fauzan (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this study is to analyze the values of Islamic character in the practice of ecological education in the non-formal school of Sanggar Anak Alam (SALAM), Nitiptayan, Bantul by examining the problem how the environmental practices carried out by the Nitiprayan Bantul Nature Studio? the ecological practices carried out by Sanggar Anak Alam?, how is the process of instilling Islamic character values in environmental practices at Sanggar Anak Alam?. based on the results of the data obtained, namely the importance of character education of Sanggar Anak Alam have a strong relationship with the substance of values in Islamic teachings which are reflected in fundamental aspects and give meaning to Islam. This study describes the development of the environment is to maintain the balance of nature and the balance of the social atmosphere. This research also confirms that the community, which also gives meaning to the relationship of spirituality with a deeper appreciation of religion, tends to have a deep concern for environmental issues. The character education process from this ecological practice can be shown from the learning cycle, namely awareness, habituation, actual training, example and reflection.